Metagenetic profiling of the bacterial communities of an intertidal pool in Kandalaksha Bay (White Sea, Russia). - Gorrasi Susanna; Pesciaroli Chiara; Paolo, Barghini; Marcella, Pasqualetti; Giovannini Valeria; Massimiliano, Fenice (Zenodo, 2019)
GORRASI, S., PESCIAROLI, C., BARGHINI, P., PASQUALETTI, M., GIOVANNINI, V., AND FENICE, M. 2019 .Metagenetic profiling of the bacterial communities of an intertidal pool in Kandalaksha Bay (White Sea, Russia). J environ prot ecol. 20(3). 1317-1324. PDF: https://docs.google.com/a/jepe-journal.info/viewer?a=v&pid=sites&srcid=amVwZS1qb3VybmFsLmluZm98amVwZS1qb3VybmFsfGd4OjIxNmIxN2VjOTU0OWFlNzQ